1990
DOI: 10.1017/s095026880004766x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of campylobacter infection in infants in western Algeria and the possible protective role of breast feeding

Abstract: SUMMARYA case-control study aimed at comparing the incidence of campylobacter infection with that of other enteropathogens in infants was performed in Oran, Western Algeria. During a one-year period, infants consulting in a health centre were included if they had acute diarrhoea. The controls comprised infants going to the same centre for vaccination. Butzler medium Virion was used to look for thermophilic campylobacters. Campylobacters were isolated in 17-7 % of the 411 patients and in 14-9 % of the 247 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 16 publications
1
17
0
5
Order By: Relevance
“…However, isolation of Campylobacter spp. from children without diarrhoea is also common in developing countries (14). In some studies, no statistically significant difference was noted in Campylobacter isolation rates in certain age groups (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, isolation of Campylobacter spp. from children without diarrhoea is also common in developing countries (14). In some studies, no statistically significant difference was noted in Campylobacter isolation rates in certain age groups (15).…”
Section: Discussionmentioning
confidence: 99%
“…Chickens can be colonized with as many as 10 9 CFU C. jejuni per gram cecal contents (43), and colonized mice can shed up to 10 6 CFU per mg feces (18). Studies of children in developing countries have shown that rates of asymptomatic carriage of Campylobacter in children are around 15% (108,131), suggesting that some acquired immunity is induced from multiple exposures during early childhood. Wheeler et al reported a rate of asymptomatic carriage of 0.7% in a population study involving adults in the United Kingdom (179).…”
Section: Pathology and Pathophysiology Of Campylobacter Infectionmentioning
confidence: 99%
“…Consistent with this, patients with defects in immunoglobulin production are more susceptible to infection. The first humoral immune mechanism encountered by Campylobacter during infection is secretory IgA (sIgA), and various studies have shown that the presence of Campylobacter-specific sIgA and serum IgA correlates with protection against disease (108,142). Also, studies of breastfed infants point to a protective role of sIgA against infection.…”
Section: Role Of Humoral Immunity In Protectionmentioning
confidence: 99%
“…Campylobacter associated diarrhoea [28]. However, time constraints and urbanisation [1] are factors associated with early termination of breast-feeding.…”
Section: Introductionmentioning
confidence: 99%